Nutritional status, feeding behavior, and oral conditions in preschool children exposed to secondhand smoke - de Sousa, Karina Guedes; de Carvalho Chaves, Samuel; de Souza Barbosa, Taís [UNESP]; Gavião, Maria Beatriz Duarte (Taylor & Francis, 2024)
This study evaluated whether the nutritional status of preschoolers is influenced by secondhand smoke. Pairs of mothers-children (N = 201) were allocated in “children exposed to secondhand smoke (ESHS)” or “not exposed (N_ESHS).” Mothers answered, “The Parental Feeding Style Questionnaire (PFSQ).” The nutritional status and oral conditions were evaluated using WHO criteria. ESHS was 3.5 more likely to have a high BMI and their mothers had 10 kg more than N_ESHS. The probability of having dental caries was 2.28 and 3.68 times greater when the mother’s BMI increases and when family/mothers were smokers, independently whether they smoke in the child’s presence.
Keywords: Children; cigarettes; food; oral health